Epistemological Approaches to Media Communication and Analysis A Postmodern Reading of Intellectual Independence and Social Transformation - BENMABROUK Fayçal; BELABES Taqiyeddine; YAHIA Takieddine (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2022)
The epistemological knowledge on which the communicative phenomenon is based in modern societies has known many changes in terms of theorizing and intellectual premises, and it had cognitive repercussions that touched multiple aspects in the field of media and communication sciences. All the modern contextual foundations on it, as we will address in this article, the influence of communication and media studies on critical European approaches that view communication as a tool for social change, the colonial past and the political context in the 1960s reinforced these social transformations that want to be embodied as intellectual independence. In this article, we will also discuss the social transformations that have contributed to the birth of new media and multiple approaches to communication research.